FOREIGN EXPERIENCE OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP (Neo Science Peer Reviewed Journal, 2023)
In the article, the world experience of small business and entrepreneurship, small business, small innovative business development, socio-economic efficiency, political programs implemented in countries, Small business development is an important factor in ensuring the increase of the share of the middle class in society, as well as economic, social and political stability in the country. such issues were analyzed.